EFFECT OF MICROPLASTIC ORAL INTAKE ON FATTY DEGENERATION AND NECROSIS OF HEPATOCYTES IN WISTAR RATS - Adinda Putri Studytasari; Yudhiakuari Sincihu; Irene Lingkan Parengkuan; Bernadette Dian Novita (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Introduction: In the human body, microplastics are considered toxic agents. Low-density polyethylene (LDPE) has very high chemical resistance, making it very difficult to be degraded by microorganisms. LDPE plastic would be degraded to a smaller size and could not be completely degraded by microorganisms. Plastic packaging made from LDPE is the most commonly found plastic waste. Microplastics may cause cell injury, especially cells in the liver, the primary organ for detoxification. Microplastic induces reactive oxygen species, which leads to oxidative stress. Prolonged exposure to microplastics leads cells unable to cope with the toxic effects. Furthermore, this process triggers fatty degeneration and necrosis. This study aims to explain the correlation between microplastic oral intake with fatty degeneration and necrosis of hepatocytes in animal models. Methods: Forty-two Wistar rats were involved and assigned to one control and five experimental groups. The experimental groups were given microplastic exposure starting from 0.0375 mg/day to 0.6 mg daily for 90 days. Results: Fatty degeneration and necrosis were observed using a light microscope with hematoxylin-eosin staining. There was a significant correlation between microplastic oral intake and hepatocyte necrosis (p<0.05). The higher the exposure dose, the more hepatocyte necrosis. In contrast, there was no correlation between microplastic exposure and fatty degeneration. Ingestion of microplastics leads to hepatocyte necrosis. Conclusion: Oral intake of LDPE microplastics with <20 µm in size for 90 days in Wistar rats leads to hepatocellular injury. Based on histopathological images, hepatocyte necrosis was more prominent than hepatocyte fatty degeneration.